The Preparation and Medical Applications of Chitosan Microspheres - Yan, Xiaoting; Song, Ganlin; Wang, Xuan; Zhao, Ying; Chen, Yu (Current Organic Chemistry, 2018)
Background: The microsphere prepared from chitosan, a natural polymeric material, has attracted considerable attentions due to the natural instincts of chitosan and microsphere structure. Objective: In the current review, the recent progress on the preparation and medical applications of chitosan microspheres would be introduced and summarized. Method: The methods for the preparation of CS microspheres were summarized, such as emulsion crosslinking method, coacervation method, precipitation method and polyelectrolyte complexation method, and so on. The tunable chemical properties possessed by CS microsphere, such as easily modified structure, and excellent biological properties including lower cytotoxicity, biocompatibility and biodegradability, would be introduced. Its medical applications based on its amazing properties in the recent years were present in detail with emphasis on the progress and advancement in drug delivery, gene therapy, bone repair, tissue engineering and wound dressing. Conclusion: It was believed that the rapid development of novel preparation technology will bring broader application prospects to CS microspheres.
Keywords: microspheres